A molecular mechanism of mouse placental spongiotrophoblast differentiation regulated by prolyl oligopeptidase. Issue 1 (4th February 2019) - Maruyama, Yuki; Kimura, Atsushi P.
Summary: In eutherian mammals, the placenta plays a critical role in embryo development by supplying nutrients and hormones and mediating interaction with the mother. To establish the fine connection between mother and embryo, the placenta needs to be formed normally, but the mechanism of placental differentiation is not fully understood. We previously revealed that mouse prolyl oligopeptidase (POP) plays a role in trophoblast stem cell (TSC) differentiation into two placental cell types, spongiotrophoblasts (SpT) and trophoblast giant cells. Here, we focused on SpT differentiation and attempted to elucidate a molecular mechanism. For Ascl2, Arnt, and Egfr genes that are indispensable for SpT formation, we found that a POP-specific inhibitor, SUAM-14746, significantly decreased Ascl2 expression, which was consistent with a significant decrease in expression of Flt1, a gene downstream of Ascl2 . Although this downregulation was unlikely to be mediated by the PI3K-Akt pathway, our results indicated that POP controls TSC differentiation into SpT by regulating the Ascl2 gene.